2012
DOI: 10.1016/j.febslet.2012.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of a cold‐active alkaline phosphatase by imipenem revealed by in silico modeling of metallo‐β‐lactamase active sites

Abstract: Edited by Miguel De la RosaWe demonstrate the inhibition of the native phosphatase activity of a cold active alkaline phosphatase from Vibrio (VAP) (IC 50 of 44 ± 4 (n = 4) lM at pH 7.0 after a 30 min preincubation) by a specific b-lactam compound (only by imipenem, and not by ertapenem, meropenem, ampicillin or penicillin G). The homologous scaffold was detected by an in silico analysis that established the spatial and electrostatic congruence of the active site of a Class B2 CphA metallo-b-lactamase from Aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Previously, we detected a promiscuous serine protease scaffold in APs using CLASP [5], and a scaffold recognizing a β-lactam (imipenem) in a cold-active Vibrio AP [18], [19]. The theoretical foundation of CLASP is that the electrostatic potential difference (EPD) in cognate pairs of active site residues is conserved in proteins with the same functionality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we detected a promiscuous serine protease scaffold in APs using CLASP [5], and a scaffold recognizing a β-lactam (imipenem) in a cold-active Vibrio AP [18], [19]. The theoretical foundation of CLASP is that the electrostatic potential difference (EPD) in cognate pairs of active site residues is conserved in proteins with the same functionality.…”
Section: Discussionmentioning
confidence: 99%
“…A recent method employs learning techniques to predict whether proteins have proteolytic activities, but has not identified any novel proteases undetected by other methods [14], [15]. CLASP unraveled a promiscuous serine protease scaffold in alkaline phosphatases (AP) [5], one of the widely studied promiscuous enzyme families [16], [17], and also a scaffold recognizing a β-lactam (imipenem) in a cold-active Vibrio AP [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…We have in the past used electrostatic congruence to detect a promiscuous serine protease scaffold in alkaline phosphatases 40 and a phosphoinositide-specific phospholipase C from Bacillus cereus 41 , and a scaffold recognizing a β -lactam (imipenem) in a cold-active Vibrio alkaline phosphatase 42, 43 . However, continuum models 44 that compute potential differences and pK a values from charge interactions in proteins 45 are sensitive to the spatial arrangement of the atoms in the structure.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work by our group has established the spatial and electrostatic congruence in cognate residue pairs of the active site in proteins with the same functionality (CLASP) 20, 21 . CLASP analysis indicated that the phosphoinositide-specific phospholipase C (PI-PLC) from Bacillus cereus has spatial and electrostatic congruence with a serine protease motif 22 .…”
Section: Introductionmentioning
confidence: 99%